2013
DOI: 10.1186/1756-9966-32-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of total intravenous and balanced inhalation anesthesia in patients with bladder cancer undergoing elective radical Cystectomy: preliminary results

Abstract: BackgroundAlthough surgery and anesthesia induce immunesuppression, remains largely unknown whether various anesthetic techniques have different immunosuppressive effects on cancer patients. Therefore, the aim of this study was to investigate the influence of total intravenous anesthesia with target-controlled infusion (TIVA-TCI) and balanced inhalation anesthesia (BAL) on the peri-operative levels of inflammatory cytokines and regulatory T cells (Tregs) in patients with bladder cancer undergoing surgery.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 45 publications
2
33
0
3
Order By: Relevance
“…22,27,28 The volatile anaesthetics isoflurane and sevoflurane modify tumour cell growth in a time-dependent manner. 29 Similar results to ours have been reported by other studies in both cancer [23][24][25] and noncancer patients. 16,30 Kvarnströ m et al 23 found no significant differences between TIVA with propofol-remifentanil and sevoflurane-fentanyl anaesthesia in IL-6 concentrations during the first 24 h after open colorectal surgery, although potential differences between fentanyl and remifentanil were not considered by the authors.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…22,27,28 The volatile anaesthetics isoflurane and sevoflurane modify tumour cell growth in a time-dependent manner. 29 Similar results to ours have been reported by other studies in both cancer [23][24][25] and noncancer patients. 16,30 Kvarnströ m et al 23 found no significant differences between TIVA with propofol-remifentanil and sevoflurane-fentanyl anaesthesia in IL-6 concentrations during the first 24 h after open colorectal surgery, although potential differences between fentanyl and remifentanil were not considered by the authors.…”
Section: Discussionsupporting
confidence: 91%
“…16,30 Kvarnströ m et al 23 found no significant differences between TIVA with propofol-remifentanil and sevoflurane-fentanyl anaesthesia in IL-6 concentrations during the first 24 h after open colorectal surgery, although potential differences between fentanyl and remifentanil were not considered by the authors. In patients with bladder cancer undergoing radical cystectomy, Sofra et al 24 reported that the plasma concentration of IL-6 was not significantly influenced in the early postoperative period by anaesthetic management (TIVA vs. sevoflurane). Deegan et al 25 found the same after breast cancer surgery when comparing sevoflurane-fentanyl with propofol-paravertebral anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fakat intraoperatif narkotik analjezik tüketim-lerinin düşük olması, kısa hastane kalış süreleri açısından kombine GEA + HKEA majör cerrahilerde üstünlük sağladığını düşünmek-teyiz. Anahtar Sözcükler: Radikal sistektomi, sitokin, immün fonksiyon, epidural anestezi Öz / Abstract manda cerrahi stres ve genel anestezinin oluşturduğu immün supresyonla zaten immün modülasyonu bozulmuş bu hasta grubunda kanser hücre yayılımı ve erken metastazların oluşum sıklığı artmaktadır (2). Tümör hücre proliferasyonu ve invazyonu spesifik sitokinlerin salınımı ile korelasyon göste-rir.…”
unclassified
“…A retrospective analysis of breast, colon and rectal cancer surgery found an improved one-and five-year overall survival of 4.7% and 5.6%, respectively, with total intravenous anaesthesia compared with sevoflurane anaesthesia [26], and preliminary data from an ongoing prospective randomised controlled trial for radical cystectomy supports these findings by demonstrating improved immune function with total intravenous anaesthesia, namely enhanced cell-mediated immunity [27].…”
Section: A Peri-operative 'Perfect Storm'mentioning
confidence: 93%